Observational study of the effect of obesity on lung volumes - Steier, Joerg; Lunt, Alan; Hart, Nicholas; Polkey, Michael I; Moxham, John (Thorax, 2014)
Background Severe obesity causes respiratory morbidity and mortality. The impact of obesity on the mechanics of breathing is not fully understood. Patients and methods We undertook a comprehensive observational study of lung volumes and elasticity in nine obese and nine normal weight subjects, seated and supine, during spontaneous breathing. Seated and supine total lung capacity (TLC) and subdivisions were measured by multibreath helium dilution method. Using balloon catheters, oesophageal (Poes) and gastric (Pgas) pressures were recorded. Transpulmonary pressure (PL) was calculated as mouth pressure (Pmouth)-Poes, and complete expiratory PL volume curves were measured. Results The obese group had a body mass index (BMI) of 46.8 (17.2) kg/m2, and the normal group had a BMI of 23.2 (1.6) kg/m2 (p=0.001). Obese and normals were matched for age (p=0.233), gender (p=0.637) and height (p=0.094). The obese were more restricted than the normals (TLC 88.6 (16.9) vs 104.4 (12.3) %predicted, p=0.033; FEV1/FVC 79.6 (7.3) vs 82.5 (4.2) %, p=0.325), had dramatically reduced expiratory reserve volume (ERV 0.4 (0.4) vs 1.7 (0.6) L, p<0.001) and end-tidal functional residual capacity (FRC) was smaller (37.5 (6.9) vs 46.9 (4.6) %TLC, p=0.004) when seated, but was similar when supine (39.4 (7.7) vs 41.5 (4.3) %TLC, p=0.477). Gastric pressures at FRC were significantly elevated in the obese (seated 19.1 (4.7) vs 12.1 (6.2) cm H2O, p=0.015; supine 14.3 (5.7) vs 7.1 (2.6) cm H2O, p=0.003), as were end-expiratory oesophageal pressures at FRC (seated 5.2 (6.9) vs −2.0 (3.5) cm H2O, p=0.013; supine 14.0 (8.0) vs 5.4 (3.1) cm H2O, p=0.008). BMI correlated with end-expiratory gastric (seated R2=0.43, supine R2=0.66, p<0.01) and oesophageal pressures (seated R2=0.51, supine R2=0.62, p<0.01). Conclusions Obese subjects have markedly increased gastric and oesophageal pressures, both when upright and supine, causing dramatically reduced FRC and ERV, which increases work of breathing.